Ferrate effectively removes antibiotic resistance genes from wastewater through combined effect of microbial DNA damage and coagulation. (15th October 2020) - Ni, Bing-Jie; Yan, Xiaofang; Dai, Xiaohu; Liu, Zhihan; Wei, Wei; Wu, Shu-Lin; Xu, Qiuxiang; Sun, Jing
Highlights: Fe(VI) treatment effectively removed ARGs from secondary wastewater effluent. Fe(VI) induced microbial DNA damage and resulted in ARG elimination. Coagulation initiated by Fe(VI) reduction products also contributed to ARG removal. Relative abundances of viable potential ARG hosts decreased after Fe(VI) treatment. Fe(VI) is promising for generating high-quality effluent with reduced ARGs risks. Abstract: The widespread of antibiotic resistance genes (ARGs) in the environment can pose severe threats to public health. The wastewater treatment plant (WWTP) is regarded as an important hotspot of ARGs in the urban environment, but the removal of ARGs through conventional treatment techniques has been proven not sufficient. In this study, ferrate (Fe(VI)) was applied for the first time to remove intracellular ARGs from the secondary effluent of the WWTP. The results showed that Fe(VI) treatment could effectively remove 15 ARGs covering eight different types as well as intI1, the most common integron important to ARGs horizontal transfer. The removal efficiencies of tested genes could reach 1.10-4.37 log at the Fe(VI) dosage of 10 mg-Fe/L, which is significantly higher than those achieved through traditional disinfection methods. The DNA gel electrophoresis suggested that Fe(VI) could induce microbial DNA damage and consequently resulted in ARGs elimination. The presence of ARGs in settled residues indicated that coagulation initiated by Fe(VI) reduction products also contributed to ARGs removal from wastewater. In addition, the viability and relative abundances of potential ARGs hosts in the wastewater were decreased after Fe(VI) treatment. This study suggested a promising prospect for applying Fe(VI) to efficiently remove ARGs from wastewater, and consequently to control their proliferation and transfer in the environment. Graphical abstract: Image, graphical abstract